High‐Curvature Transition‐Metal Chalcogenide Nanostructures with a Pronounced Proximity Effect Enable Fast and Selective CO2 Electroreduction - Gao, Fei‐Yue; Hu, Shao‐Jin; Zhang, Xiao‐Long; Zheng, Ya‐Rong; Wang, Hui‐Juan; Niu, Zhuang‐Zhuang; Yang, Peng‐Peng; Bao, Rui‐Cheng; Ma, Tao; Dang, Zheng; Guan, Yong; Zheng, Xu‐Sheng; et al. (Angewandte Chemie International Edition, 2020)
A considerable challenge in the conversion of carbon dioxide into useful fuels comes from the activation of CO2 to CO2.− or other intermediates, which often requires precious‐metal catalysts, high overpotentials, and/or electrolyte additives (e.g., ionic liquids). We report a microwave heating strategy for synthesizing a transition‐metal chalcogenide nanostructure that efficiently catalyzes CO2 electroreduction to carbon monoxide (CO). We found that the cadmium sulfide (CdS) nanoneedle arrays exhibit an unprecedented current density of 212 mA cm−2 with 95.5±4.0 % CO Faraday efficiency at −1.2 V versus a reversible hydrogen electrode (RHE; without iR correction). Experimental and computational studies show that the high‐curvature CdS nanostructured catalyst has a pronounced proximity effect which gives rise to large electric field enhancement, which can concentrate alkali‐metal cations resulting in the enhanced CO2 electroreduction efficiency. The needle has landed: CdS nanostructures with sharp tips can generate large electric fields that lead to increased CO2 concentrations for CO2‐to‐CO conversion. The localized electric fields are significantly enhanced when two nanoneedles are in close proximity. These advantages result in CO2 electrocatalytic reduction with a 95.5±4.0 % CO Faraday efficiency.